ON (ALPHA ,BETA)-FUZZY IDEALS OF TERNARY SEMIGROUPS - Bijan Davvaz (IndoMS, 2013)
In this paper, we introduce the concept of generalizedfuzzy ideals in ternary semigroups, which is a generalization of the fuzzyideals of semigroups. In this regard, we define (α ,β )-fuzzyleft (right, lateral) ideals, (α ,β )-fuzzy quasi-ideals and (α ,β )-fuzzy bi-ideals and invetigate some related properties ofternary semigroups. Special concentration is paid to (,q)-fuzzy left (right, lateral) ideals, (,q)-fuzzy quasi-idealsand (,q)-fuzzy bi-ideals. Finally, wecharacterize regular ternary semigroups in terms of these notions.DOI : http://dx.doi.org/10.22342/jims.19.2.120.123-138